KEPEMIMPINAN DAN MANAJEMEN KEPALA SEKOLAH DALAM MENYELSAIKAN PERMASALAHAN DI SEKOLAH MENENGAH KEJURUAN - AL Hafidz, Miftah; Zuhda Bahtiar, Fahmy; Burhan, Nurul (Information Technology Education Department, 2024)
The principal in this context plays a key role as a leader who must be able to improve the quality of human resources, especially in the context of Vocational Education. This research involved in-depth interviews with the Principal of SMK Pembaharuan Purworejo, using a qualitative approach. SMK Pembaharuan Purworejo has several problems in facing challenges, such as declining student achievement, morality issues, and challenges in preparing students for college. To overcome these problems, the Principal has implemented several strategies in both leadership and management styles. These include evaluating previous policies, providing motivation and facilities to students and teachers for their development, as well as to increase social awareness, and deepening the material with the help of peer tutors.